Assessment of undernutrition using composite index of anthropometric failure among children less than 5 years in an urban slum, Visakhapatnam - Namburi, Naga Sowjanya; Seepana, Madhavi (International Journal Of Community Medicine And Public Health, 2018)
Background: Under nutrition continues to be a major public health problem in India despite years of incessant preventive measures. Composite index of anthropometric failure (CIAF) provides the burden of under nutrition as a single measure and helps in detection of children with multiple anthropometric failures. The objectives of this study are to assess the prevalence of under nutrition using CIAF as compared to conventional indicators and to identify the risk factors associated with Anthropometric Failure. Methods: This was a community based, cross sectional descriptive study on Under 5 children done in the urban slum area under Allipuram Urban Health Centre, Visakhapatnam, A.P. Anthropometric measurements (height, weight and mid upper arm circumference) were taken and mothers of the study children were interviewed to obtain relevant information. WHO Z-score system and the CIAF were used to estimate the magnitude of under-nutrition. Results: Out of 100 children, 56 children were suffering from under nutrition according to CIAF. Analysis of various factors showed that low birth weight, lesser duration of breast feeding, low education level of mother, over crowding and low socio economic status were significantly associated with under nutrition assessed by CIAF. Conclusions: CIAF provides the actual prevalence or proportion of undernourished children in a community. So CIAF must be included in regular recordings of health status of children. The study also reinforces the importance of appropriate maternal care, proper infant and child feeding practices and family planning services in prevention of under nutrition.